La actividad probatoria en el procedimiento administrativo: su diferencia con la del código procesal civil - Armas Cruz, Julia Nancy (2010)
The present thesis to choose the lawyer title focuses the thematic one of the Theory of the Test in the Procedural Administrative Right: its conceptual content, its probatory differences with the test in the civil process, means and the probatory performance. One analyzes the differences between the administrative test and the civil procedural test, from the autonomy anticipated in the Art. 5, numeral 1, of the T.P. of the Law N° 27444; maintaining at the end of investigation, which the probatory means in the administrative scope are identical to which it is anticipated in the General Theory of the Right, and therefore in the procedural civilian; but they are different in the administrative right, assuming characteristic special like are the different position from the parts, the purpose different in the guarantee function, the prevalence of the public interest, the nonoperativity of the preclution and the informalation, that is reflected in the principles of the informalismo, office and the material truth; that they are pillars in the administrative procedure